On the measurement of product quality in intra-industry trade: an empirical test for China - Abdul Karim, Mohd Azhar; Elliott, Robert J. R.; Liu, Junting (Elsevier, 2008)
A relatively recent development in the intra-industry trade (IIT) literature is the measurement of the simultaneous import and export of quality-differentiated products, commonly known as vertical and horizontal IIT. A recent paper from Azhar and Elliott [Azhar, A. K. M. & Elliott, R. J. R. (2006), On the Measurement of Product Quality in Intra-Industry Trade, Review of World Economics, Vol 142 no 3, pp 476–495] analyses various approaches for disentangling vertical and horizontal IIT and suggests a complementary methodology. To investigate the robustness and sensitivity of the existing approaches we examine data on the nature of trade flows between China and its East Asian neighbours and show that in 2002 China tended to export low quality versions of its manufactured goods to Malaysia, Thailand and the Philippines.